2011
DOI: 10.1097/jnn.0b013e3182212a1d
|View full text |Cite
|
Sign up to set email alerts
|

A Nursing Pilot Study on Bedside Reporting to Promote Best Practice and Patient/Family-Centered Care

Abstract: Bedside reporting saves money, improves patient and nurse satisfaction, and is a more comprehensive approach to change-of-shift reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…Nurses often complain about getting out late and the time it takes to give report. Results from a pilot study where bedside reporting was implemented show that the number of overtime shift hours per nurse per month was statistically higher for the period before implementation than after implementation of bedside reporting (Tidwell et al, 2011). Bedside reporting takes less time, which translates into financial savings.…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Nurses often complain about getting out late and the time it takes to give report. Results from a pilot study where bedside reporting was implemented show that the number of overtime shift hours per nurse per month was statistically higher for the period before implementation than after implementation of bedside reporting (Tidwell et al, 2011). Bedside reporting takes less time, which translates into financial savings.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Patients are also always aware of who their nurse is on every shift and don't feel "there is no one around" during shift change (Tidwell, et al, 2011).…”
Section: Benefitsmentioning
confidence: 99%
“…11 The majority of published studies have focused on the implementation of bedside handoffs 3,5,[12][13][14] and nurse perceptions of the process. 9,14,15 Several of the studies that reported on implementation and nurse perceptions also included anecdotal findings of patient perceptions. Webster 16 concluded that patients and their families "appear more relaxed and team members appear highly interactive/communicative with patients during the hand-over process."…”
mentioning
confidence: 96%
“…3,4 Reports of patients' perspectives of bedside handoff have been qualitative, anecdotal, or have used indirect measurement tools such as the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) or proprietary surveys. [5][6][7][8][9] While information gathered by these methods provides valuable feedback to hospitals and their nursing staffs, it is possible that reports of increases in positive responses to these tools could be due to a number of factors and not only the practice of bedside handoffs. The purpose of this study was to identify patients' perceptions of the bedside handoff by means of direct and quantitative measurement.…”
mentioning
confidence: 99%
“…1 Allowing patients to be a part of the ToC process by using "bedside" handoffs has been shown to have positive outcomes for patients and the health care team, including increased patient satisfaction and patient involvement in their own care, with the potential for improved patient safety. [24][25][26] A physician exchange of information at bedside was shown to be a patient-preferred methodology that encourages patients to participate in their care. 27 …”
Section: Barriers To Effective Tocsmentioning
confidence: 99%